An Integrated Formulation of Zernike Invariant for Mining Insect Images - Norsharina Abu Bakar; Siti Mariyam Shamsuddin; Maslina Darus (Fakultas Ilmu Komputer, Universitas Sriwijaya, 2011)
This paper presents mathematical integration of Zernike Moments and United Moment Invariant for extracting printed insect images. These features are further mining for granular information by investigating the variance of Interclass and intra-class. The results reveal that the proposed integrated formulation yield better analysis compared to conventional Zernike moments and United Moment Invariant.